Replacement cost depreciation and cash flow requirements - R. C. Doenges; W. D. Hamman; I. J. Lambrechts (South African Journal of Business Management, 1990)
In this article a framework is developed to test whether depreciation based on replacement cost meets cash flow requirements. It also indicates both the extent to which depreciation based on replacement cost can be linked to depreciation based on historical cost and the factors which should be considered in the calculation of the ratio of replacement cost depreciation to historical cost depreciation. These aspects are of importance to most enterprises and of particular importance to price-controlled enterprises. The most significant findings are that: there is no need to provide for backlog depreciation; additional depreciation needs only be provided to the extent that equity financing is used; and the ratio of replacement cost depreciation to historical cost depreciation is a function of the inflation rate, lives of assets and the applicable gearing ratios.
Keywords: 650